Adaptive instantaneous frequency ridge extraction based on target tracking for frequency-modulated signals. (September 2022) - Hu, Yue; Tu, Xiaotong; Li, Fucai; Zhu, Yanping; Lu, Jing
Abstract: The instantaneous frequency (IF) is an important feature for the analysis of non-stationary signals. However, extracting multiple IF ridges, crossing IF ridges, and discontinuous IF ridges simultaneously is still a challenging task. To solve this problem, an adaptive IF ridge extraction method is proposed. This method regards the IF ridge values at each time point as targets to be tracked. The tracking targets are defined as three states: survival, death, and birth. Firstly, the potential peaks in the time–frequency representation are found to reduce the noise effect. Secondly, an adaptive penalty function is constructed to determine the target state and track the ridge target. Thirdly, the crossing ridges are separated base on the slope information. This method is capable of simultaneously extracting multiple IF ridges, crossing IF ridges, and discontinuous IF ridges. The performance of the proposed method is investigated by a simulated signal and two experimental signals. Highlights: The proposed method can simultaneously extract multiple IF ridges, crossing IF ridges, and discontinuous IF ridges. The proposed method regards the IF ridge values as targets to be tracked. The tracking targets are defined as three states: survival, death, and birth. The proposed method can adaptively estimate the ridge number, accurately estimate the birth and the death of a discontinuous ridge, and allocate the follow-up targets to the appropriate ridge after the crossing point. The simulation and the experiments have verified the effectiveness of the proposed method.